Pre-oviposition behavior of Aedes aegypti in the field: first report of eggs laying on water surface in an artificial breeding site in the city of Rio de Janeiro - Dias Wermelinger, Eduardo; Pacheco Ferreira, Aldo; Vilanova Benigno, Ciro; de Medeiros Meia, Antonio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
This study presents the first report of Aedes aegypti laying eggs on the water surface of an artificial breeding site in the field. This report occurred in the city of Rio de Janeiro inside a white bucket containing 11 liters of rainwater. Conspecific larvae had previously been found in this bucket. From the 219 eggs obtained, 135 (61.6%) were laid on the water and 84 (38.3%) on the border of the bucket. Larvae (4th instar) and adults obtained from the eggs were identified as A. aegypti. This behavior may influence the population dynamics of A. aegypti and expands the knowledge about the species adaptation. This report confirms the species’ ability to lay eggs on the water surface of artificial breeding sites in the field and suggests the hypothesis that pheromones in the water may influence the females to lay eggs on water. KEY WORDS: Ethology; Aedes aegypti; adaptation; disease vectors; mosquito vectors.